Model Pembelajaran Peer Teaching untuk Meningkatkan Maharah Qira’ah Siswi Kelas X Pondok Pesantren Tahfizhul Qur’an Daarul Fath Putri – Boyolali - Muhammad Rafik (Thulabuna: Jurnal Pendidikan Bahasa Arab, 2022)
In the world of education, it is undeniable that a learning method or model greatly influences the success of a learning process, including Arabic language learning. The peer tutoring or peer teaching model is one of the learning models that can be used to improve Arabic learning outcomes, especially the mahārah qirā’ah (reading skills). his study aims to improve the Arabic mahārah qirā’ah of tenth-grade female students at Pondok Pesantren Tahfizhul Qur’an Daarul Fath Putri Boyolali in the 2022/2023 academic year by applying the peer tutoring or peer teaching learning model. This research uses the spiral cycle Classroom Action Research (CAR) model by Kemmis and McTaggart. Data collection methods used in this study include observation, interviews, and documentation. The data analysis method used is a combined analysis method between qualitative and quantitative research, or Mixed Methods Research. The results of this study show that the application of the peer tutoring or peer teaching learning model to improve mahārah qirā’ah among the tenth-grade students at PPTQ Daarul Fath Putri is very effective and has been proven to enhance students’ learning outcomes, particularly in mahārah qirā’ah. This is evident from the following results: 1)In Cycle I, the average oral test score of the students was 74, with 13 students (out of 25) achieving mastery, or 52%, while the average written test score was 78.4, with 15 students (out of 25) achieving mastery, or 60%. 2)In Cycle II, the average oral test score of the students increased to 78.5, with 22 students (out of 25) achieving mastery, or 88%, representing a 36% increase from the oral test mastery rate in the post-test of Cycle I. Meanwhile, the average written test score rose to 82.6, with 23 students (out of 25) achieving mastery, or 92%, representing a 32% increase from the written test mastery rate in the post-test of Cycle I.